Development of the Burong Mandi tourist village through a digital-based sustainable tourism model - Handika Akmal Ramadani; Muamar Faturohman; Ririn Apriyani; Lely Badriyatul Hasanah; Faruq Damar Fattah; Nunung Nurjanah; Muhammad Fiqri Lewa; Deta Cerelia Berliana; Karunia Bintang; Muhammad Renaldi; Dita Nur Febiyanti; Mohamad Anwar; Haiyudi Haiyudi (Universitas Muhammadiyah Magelang, 2024)
Burung Mandi, a village blessed with diverse tourist attractions ranging from beaches to hills and mountains, faces challenges in promoting sustainable tourism while leveraging digital approaches. To address these gaps, this community outreach program aimed to enhance the understanding of tourism stakeholders, including village officials and Pokdarwis (tourism awareness groups), on the principles of digital sustainable tourism. The program employed a training methodology, encompassing presentations and mentorship sessions. The outcomes of these activities included the creation of a tourist map, tourism packages, and a YouTube channel. Additionally, evaluation results indicated a significant improvement in the understanding of digital sustainable tourism among the participants.